Tinjauan Perlakuan Aset Tetap Sesuai SAK ETAP No. 15 - Suryadi, Erni; Putri, Wulan Wahyuni Rossa (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Companies which value and number of fixed assets are sufficiently material, errors in determining and classifying acquisition prices, expenditures during the use and termination of fixed assets will affect the overall financial statements. Therefore, the accuracy in recording fixed assets greatly influences the reliability of the presentation in financial statements. This study aims to determine how the recognition and measurement of fixed assets applied in PT Suryakabel Cemerlang, as well as the presentation of fixed assets in financial statements at PT Suryakabel Cemerlang. Data collection is done through observation, interviews and documents to the parties concerned. This research is descriptive qualitative. The results showed that the accounting treatment of fixed assets at PT. Suryakabel Cemerlang has not fully complied with SAK ETAP No. 15. But the recognition and measurement of fixed assets is in accordance with SAK ETAP No. 15, but no record of the termination of fixed assets has yet been made. This causes the acquisition price and accumulated depreciation of fixed assets presented in the balance sheet to be greater. Based on the results of the study it can be concluded that the accounting treatment of fixed assets must be based on SAK ETAP No. 15 in order to present accurate financial reports so that they can be used as one of the basis for future decision making. Keywords : treatment of fixed assets, SAK ETAP No. 15